Aryl radical cyclization with alkyne followed by tandem carboxylation in methyl 4-tert-butylbenzoate-mediated electrochemical reduction of 2-(2-propynyloxy)bromobenzenes in the presence of carbon dioxide. Issue 31 (4th August 2016) - Katayama, Asahi; Senboku, Hisanori; Hara, Shoji
Abstract: Constant current electrolysis of 2-(2-propynyloxy)bromobenzenes in DMF using an undivided cell equipped with a Pt cathode and an Mg anode in the presence of carbon dioxide and an electron transfer mediator, methyl 4- tert -butylbenzoate, resulted in aryl radical cyclization with a carbon–carbon triple bond followed by fixation of two molecules of carbon dioxide to give 2, 2-ring-fused succinic acid derivatives in moderate to good yields. Dihydrobenzofuran, indoline, dihydrobenzothiophene, and indane as well as tetrahydropyran skeletons were successfully constructed by aryl radical cyclization, and unique tandem carboxylation successively occurred to produce succinic acids. One of the resulting succinic acid derivatives, 3-carboxy-2, 3-dihydrobenzofuran-3-ylacetic acid, was successfully applied to the synthesis of a novel spiro compound consisting of 2, 3-dihydrobenzofuran and γ-butyrolactone at each C3 position in two steps in high yield. Graphical abstract: